(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Congenital heart defects (CHD) occupy one of the leading places among congenital anomalies of development and are a significant cause of infant mortality and disability in the child population worldwide: according to the World Health Organization, the incidence of CHD is 8–12 cases per 1000 live births, and about 1.35 million children with this pathology are born annually in the world [1, 2]. Among all forms of CHD, defects are of particular clinical importance, accompanied by blood discharge from left to right, such as ventricular septal defect, atrial septal defect, patent ductus arteriosus, and atrioventricular canal, which together account for up to 40–50% of all CHD and, in the absence of timely surgical correction, are naturally complicated by the development of pulmonary arterial hypertension (PAH) [3, 4]. According to large epidemiological studies, CHD-associated PAH is detected in 1.6–12.5 per million population, while in patients with uncorrected malformations with pulmonary hypervolemia, pulmonary hypertension is formed in 30–50% of cases within the first two years of life [5, 6]. An extreme and irreversible manifestation of this complication is Eisenmenger syndrome, in which the pressure in the pulmonary artery reaches the systemic level, blood discharge becomes right-left and surgical correction of the defect is impossible; The survival rate of such patients is significantly reduced, and the median life expectancy does not exceed 40–50 years [7, 8].